SELF-DEVELOPMENT IN STRUCTURE OF SELF-IMPROVEMENT OF THE FUTURE TEACHER OF MUSIC (VIOLINIST) - Zavalko К.V. (Pedagogy of Higher and Secondary Education, 2007)
In article process of self-improvement of the future teacher of music, in particular its component - self-development is considered. Directions of self-development are allocated and analyzed.